Finite Element Framework for Efficient Design of Three Dimensional Multicomponent Composite Helicopter Rotor Blade System - Arunabha M. Roy (Eng, 2021)
In the present study, a three-dimensional finite element framework has been developed to model a full-scale multilaminate composite helicopter rotor blade. Tip deformation and stress behavior have been analyzed for external aerodynamic loading conditions and compared with the Abaqus FEA model. Furthermore, different parametric studies of geometric design parameters of composite laminates are studied in order to minimize tip deformation and maximize the overall efficiency of the helicopter blade. It is found that these parameters significantly influence the tip deformation characteristic and can be judiciously chosen for the efficient design of the rotor blade system.